A child an hour: burden of injury deaths among children under 5 in Pakistan. Issue 11 (16th August 2013) - Razzak, Junaid A; Khan, Uzma Rahim; Zia, Nukhba; Azam, Iqbal
Abstract : Background: Globally, more than 875 000 children under the age of 18 die due to injury every year. The rate of child injury death is 3.4 times higher in low-income and middle-income countries than in high-income countries. Objectives: To study injury mortality burden among children under the age of 5 in Pakistan. Methods: Demographic and Health Survey in Pakistan was conducted from September 2006 until February 2007. It included 95 000 households, out of which 3232 households had death of a child under the age of 5 from January 2005 onwards. The Child Verbal Autopsy Questionnaire (CVAQ) was administered to these households with a response rate of 96%. Results: For age group 0–5 years, injury was the sixth leading cause of death and was responsible for 2.5% of all deaths (n=73). For age group 1–5 years, injury was found to be the third leading cause of death (11%) after diarrhoea (18%) and pneumonia (17%). The overall under fives mortality rate due to injury was estimated at 39.5 per 100 000 per year in Pakistan. Drowning (22%), road traffic injuries (12%), burns (11%) and falls (10%) were the most common types of injury. The mortality rate was twice as high in rural areas (32 per 100 000; 95% CI 18 to 45), compared to the urban areas (15 per 100 000; 95% CI 0.3 to 29). Conclusions: Injury is the third leading cause of deaths among children 1–5 in Pakistan. The burden is twice as high in rural areas.